2006
DOI: 10.1152/ajpheart.00405.2005
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of aging on limb blood flow in humans

Abstract: Aging appears to attenuate leg blood flow during exercise; in contrast, such data are scant and do not support this contention in the arm. Therefore, to determine whether aging has differing effects on blood flow in the arm and leg, eight young (22 Ϯ 6 yr) and six old (71 Ϯ 15 yr) subjects separately performed dynamic knee extensor [0, 3, 6, 9 W; 20, 40, 60% maximal work rate (WR max)] and handgrip exercise (3, 6, 9 kg at 0.5 Hz; 20, 40, 60% WR max). Arterial diameter, blood velocity (Doppler ultrasound), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
178
7

Year Published

2006
2006
2016
2016

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 145 publications
(196 citation statements)
references
References 42 publications
(53 reference statements)
11
178
7
Order By: Relevance
“…Ten patients with COPD were enrolled based on spirometric evidence of moderate to severe airflow obstruction [FEV 1/FVC Յ 0.7 (10)], as assessed by standard pulmonary function tests performed during an initial visit to the laboratory. General anthropometric characteristics, including thigh volume, which was used to estimate quadriceps muscle mass (16), were also determined during this visit. Resting arterial blood analyses, collected in a parallel study in which the current subjects took part, are also presented here to better characterize the patients.…”
Section: Methodsmentioning
confidence: 99%
“…Ten patients with COPD were enrolled based on spirometric evidence of moderate to severe airflow obstruction [FEV 1/FVC Յ 0.7 (10)], as assessed by standard pulmonary function tests performed during an initial visit to the laboratory. General anthropometric characteristics, including thigh volume, which was used to estimate quadriceps muscle mass (16), were also determined during this visit. Resting arterial blood analyses, collected in a parallel study in which the current subjects took part, are also presented here to better characterize the patients.…”
Section: Methodsmentioning
confidence: 99%
“…To illustrate, recent studies that assessed FMD in the arm and leg (5,19,33,34) have concluded that limb differences exist in FMD, possibly as a consequence of differences in activity level and/or arterial pressure. However, limb differences may, in part, also relate to baseline artery size, since arteries in the leg and arm differ in dimension.…”
Section: Clinical Relevancementioning
confidence: 99%
“…For each 45-second ultrasound Doppler segment, V mean was averaged across 15-second intervals of each recorded clip, with intima-to-intima diameter measurements evaluated during diastole, as described previously. 20,21 Because of the anticipated decline in maximal knee-extensor exercise capacity in older subjects, the a priori design was to assess responses at similar relative exercise intensities. However, posthoc analysis of responses using a single absolute work rate of 10 W was also performed to evaluate potential age-related differences at comparable levels of leg O 2 consumption.…”
Section: Data Analysis and Statisticsmentioning
confidence: 99%